Pengaruh Event Picnic Over The Hill Volume 1-3 Terhadap Keputusan Berkunjung ke Kawasan Parapuar, Labuan Bajo (Jurnal Destinasi Pariwisata, 2025)
Labuan Bajo is a super-priority tourism destination that has undergone significant development in terms of infrastructure, tourist arrivals, and intensive promotional strategies. In response to this growth, a new tourism area named Parapuar is being developed and managed by the Badan Pelaksana Otorita Labuan Bajo Flores (BPOLBF) as part of efforts to strengthen the tourism appeal within the region. To promote this area, BPOLBF organized an open-air music and picnic event called Picnic Over The Hill (POTH), held in three consecutive volumes. This study aims to analyze whether the implementation model of POTH Volumes 1–3 significantly influences travel decisions among event attendees. A quantitative descriptive method was applied using multiple regression analysis. Data were collected from 100 respondents who had attended one of the POTH events, with variables including Festive Spirit (X1), Uniqueness (X2), Authenticity (X3), Hospitality (X4), Theming (X5), and Symbolism (X6), and analyzed using SPSS version 26.0 for Windows.The F-test results (F = 14.26 > 2.21) indicate that all variables simultaneously have a significant effect on travel decision-making. Meanwhile, the t-test shows that four variables—Festive Spirit, Uniqueness, Hospitality, and Theming—have a partially significant influence, whereas Authenticity and Symbolism do not. These findings suggest that the POTH model successfully generates visitor interest through its vibrant atmosphere, unique experiences, quality hospitality, and engaging themes. However, improvements are still needed in authenticity and symbolic elements. Overall, the event has proven effective in enhancing visitor engagement and plays a strategic role in shaping the image of Parapuar as a developing tourism destination.